From Structural Violence to Criminal Event: A Cross-National Synthesis of Femicide Reporting in Media Discourse - Ratna Puspita (Lingkar Studi Komunikasi (LISKI), 2026)
This study examines the gap between the increasing visibility of femicide in media coverage and the limited recognition of its structural dimensions. It synthesizes 16 international studies (2016–2025) to develop an analytical framework for examining femicide reporting, with relevance to the Indonesian context. Using a narrative literature review, the study integrates findings on terminology, framing, representation, discursive authority, and sensationalism. The findings show that femicide reporting operates along a continuum between structural politicization and individual depoliticization. Across contexts, coverage is characterized by de-gendered terminology, episodic and legal-procedural focus, victim-blaming, perpetrator rationalization, reliance on institutional sources, and sensationalism. These patterns suggest that increased media visibility does not necessarily enhance recognition of structural gender inequality, but often reinforces individualized interpretations of violence. The study proposes six analytical dimensions as a systematic framework for cross-context analysis and more gender-sensitive journalism.